1996
DOI: 10.1006/faat.1996.0005
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Evaluation of Fluvastatin, an HMG–CoA Reductase Inhibitor, in Beagle Dogs and Rhesus Monkeys

Abstract: Fluvastatin is a potent synthetic competitive inhibitor of beta-hydroxy-beta-methyl-glutaryl-coenzyme A (HMG-CoA) reductase, the rate-limiting enzyme in the biosynthetic pathway for hepatic cholesterol synthesis. The therapeutic indication is reduction of elevated total and low-density lipoprotein cholesterol levels. Results from four toxicity studies in beagle dogs and one study in rhesus monkeys following oral administration of fluvastatin are reported. In two 26-week dog studies, doses were 0, 1, 8, or 48 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…At high dosage levels in dogs treated with some HMG-CoA reductase inhibitors, significant evidence of liver pathology is observed (Walsh and Rockwell, 1999;Hartman et al, 1996). With other reductase inhibitors, elevations in serum transaminase activity were observed in dogs in the absence of any morphologic abnormalities in the liver or other tissues Gerson et al, 1989;Gerson et al, 1991).…”
Section: Effects That Are Clearly Related To Exaggerated Biochemical mentioning
confidence: 99%
See 2 more Smart Citations
“…At high dosage levels in dogs treated with some HMG-CoA reductase inhibitors, significant evidence of liver pathology is observed (Walsh and Rockwell, 1999;Hartman et al, 1996). With other reductase inhibitors, elevations in serum transaminase activity were observed in dogs in the absence of any morphologic abnormalities in the liver or other tissues Gerson et al, 1989;Gerson et al, 1991).…”
Section: Effects That Are Clearly Related To Exaggerated Biochemical mentioning
confidence: 99%
“…High doses of the HMG-CoA reductase inhibitors atorvastatin or fluvastatin given to beagle dogs can result in hepatocellular degeneration or necrosis, inflammation and necrosis of gallbladder epithelium and evidence of bile duct hyper- plasia (Corsini et al, 1966;Hartman et al, 1996;Walsh et al, 1996). With other statins, administration to dogs for extended periods of time (up to 2 years) with high doses results in significant elevations of serum transaminase activity in the absence of evidence of hepatic morphologic changes detected either by light or electron microscopy Gerson et al, 1989Gerson et al, , 1991.…”
Section: Effects That Are Clearly Related To Exaggerated Biochemical mentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could be due to relatively increased concentrations of AT in bile and gallbladder, since AT is excreted primarily via bile. It is also possible that low cholesterol levels affected bile composition, since cholesterol is the immediate precursor to bile acids (20,25 (10).…”
Section: Moribund and Week 52mentioning
confidence: 99%
“…Full details of this study will be reported elsewhere. Briefly, beagle dogs were given 0, 10, 40, or 120 mg/kg of AT in gelatin capsules daily (10 (23), and procedures and results of semen and sperm analyses will be reported separately (6).…”
Section: Introductionmentioning
confidence: 99%